GW24-e3612 Effects of prescription of Jiashen on ventricular remodelling and infiltration of monocyte/macrophages in the early period after myocardial infarction in rats. (1st October 2013) - Liu, Yanyan; Wang, Youping; Xie, Shiyang; Li, Bin; Zhu, Mingjun
Abstract : Objectives: This study was designed to test the hypothesis that PJS modulates inflammatory processes to prevent cardiac functional deterioration and reduce ventricular remodelling after MI. Methods: Male Sprague-Dawley rats (9-10 weeks) were subjected to sham-MI or MI by ligating the left anterior descending coronary artery for 1 and 4 weeks. The rats were divided into five groups: sham, MI, PJS (3 g/kg/day), PJS (6 g/kg/day), and losartan (an AT1 antagonist, 10 mg/kg/day). The vehicle, PJS, or losartan was given by oral gavage once a day after MI. Cardiac functions were determined by echocardiographic measurements at 1 and 4 weeks after MI. Fibrinogen at the site of infarction and in ischaemic myocardium were determined by Masson staining. Results of quantitative analysis were used to detect the level of hydroxyproline. Monocyte/macrophages expression was detected by immunohistochemistry staining and quantitative analysis. Results: 1) The echocardiographic measurement showed that Both LVEDd and LVESd in the PJS-6 and Losartan groups were significantly shorter than in the MI group at both week 1 and week 4 post-MI. Both FS and EF were well-maintained in the PJS-6 and Losartan groups than in the MI group at both week 1 and week 4 post-MI. 2) Masson trichrome staining of cardiac sections: At 1 and 4 weeks after myocardial infarction, fibrinogen proliferation was much more obvious in MI group than in sham operation group.a detectable reduction of fibrinogen with PJS-6 and Losartan groups at the site of infarction was not found but was reduced at ischaemic sites. Results of quantitative analysis shows: compared to the MI group, the PJS-6 and losartan groups significantly decrease at both the infarction and ischaemia areas the level of fibrinogen. 3) Immunohistochemical results of monocyte/macrophages shows: At 1 and 4 weeks after myocardial infarction, monocyte/macrophages was much more obvious in MI group than in sham operation group compared to the MI group, the PJS-6 and losartan groups significantly decrease at both the infarction and ischaemia areas of monocyte/macrophages. Conclusions: Our studies demonstrate that the PJS improves cardiac function, inhibits cardiac remodelling and suppresses infiltration of monocyte/macrophages after myocardial infarction. The data indicate that PJS inhibits its ventricular remodelling possibly via inhibiting infiltration of monocyte/macrophages. The results suggest that PJS may have a promising potential for the prevention and treatment of MI.